Playing unfair the media image of the female athlete - King, Kenyong; Media Education Foundation ([Northampton, Mass.] : Media Education Foundation, 2002)
It has been 30 years since Title IX legislation granted women equal playing time, but the male-dominated world of sports journalism has yet to catch up with the law. Coverage of women's sport lags far behind men's, and focuses on female athletes femininity and sexuality over their achievements on the court and field
Title from title screen
Executive producer, Loretta Alper ; editor, Kenyon King ; camera, Kelly Garner ; music, Stone Coyotes ; sound engineer, Thom Monahan
Keywords: Women athletes; Mass media and sports; Sex role in mass media; Gender roles